Desarrollo de carrocería aerodinámica para monoplaza eléctrico de la escudería ara de la Regional Antioquia en el marco de la formula SENA ECO 2013 - 2014 (2016)
In the automotive industry, high-performance daily seeks to optimize each of the systems that make up the vehicle, taking into account design, materials and / or manufacturing method. Thus, in this article the development of the body for an electric vehicle car, designed under aerodynamic conditions defined by finite element modeling and made of composite materials under the resin infusion technique is presented. A lightweight body that provides the vehicle proper downforce to achieve maximum efficiency and performance in their participation in the competition Formula SENA ECO is obtained